2020
DOI: 10.20944/preprints202007.0260.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trace Element, Immune and Opioid Biomarkers of Unstable Angina, Increased Atherogenicity and Insulin Resistance: Results of Machine Learning

Abstract: Background: Aberrations in endothelial cells, immune and oxidative pathways are associated with atherosclerosis (ATS) and unstable angina (UA). The role of trace elements, minerals, and the endogenous opioid system (EOS) in UA are less well established. Methods: We measured lipid, insulin resistance (IR), and immune, trace element (copper and zinc), mineral (magnesium, calcium), EOS (β-endorphin and mu-opioid receptor (MOR)) and antioxidant (vitamin D3) biomarkers in patients with ATS (n=60) and UA (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Nevertheless, comorbid depressive ratings in unstable angina were not only associated with atherogenicity, insulin resistance, lowered zinc but also with increased IL-6 and calcium levels [122].…”
Section: Biomarkers Of Affective Symptoms Due To T2dmmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, comorbid depressive ratings in unstable angina were not only associated with atherogenicity, insulin resistance, lowered zinc but also with increased IL-6 and calcium levels [122].…”
Section: Biomarkers Of Affective Symptoms Due To T2dmmentioning
confidence: 91%
“…The latter may, however, be explained by specific effects of calcium mineralization of arteries and calcification of plaques in unstable angina [122].…”
Section: Biomarkers Of Affective Symptoms Due To T2dmmentioning
confidence: 99%
“…5,6 Recently, we found that ATS may be discriminated from normal controls by using a combination of different biomarkers in machine learning models, namely an increased HOMA-IR index, IL-6, IL-10 (a negative immune regulatory cytokine), β-endorphin, copper and magnesium, and lower zinc. 24 Moreover, ATS with UA was significantly discriminated from ATS without UA by increased levels of triglycerides (TG), IR, IL-10, β-endorphin, and mu-opioid receptors (MOR), and lowered vitamin D3, another antioxidant. 24 In this respect, it is interesting to note that increased IL-10 may play a protective role in ATS and in major depression.…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, ATS with UA was significantly discriminated from ATS without UA by increased levels of triglycerides (TG), IR, IL-10, β-endorphin, and mu-opioid receptors (MOR), and lowered vitamin D3, another antioxidant. 24 In this respect, it is interesting to note that increased IL-10 may play a protective role in ATS and in major depression. 25,26 Indeed, IL-10 is a major component of the compensatory immune regulatory system (CIRS), which attenuates the IRS in chronic immune disorders including ATS and major depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation